Pansitopenia: Challenges Of Approach And Case Handling In Peripheral Hospitals - M. Hikmawan Priyanto; Ibnu Mas’ud (Eduvest - Journal of Universal Studies, 2024)
Pancytopenia is a hematological condition characterized by a decrease in three blood cell lines: erythrocytes, leukocytes, and platelets. This condition is not an independent disease, but a manifestation of various underlying diseases. Pancytopenia can be caused by impaired blood cell production in the bone marrow or increased destruction of blood cells in the periphery. Precise and prompt identification of the etiology is essential, given that pancytopenia can be life-threatening if not treated properly. This study aims to analyze and identify the causes of pancytopenia in patients at Batang Regency Hospital, as well as provide recommendations for appropriate treatment based on the etiology found. The methods used were clinical observation, laboratory examination, and diagnostic imaging in a 58-year-old patient with the main complaint of weakness and a history of pancytopenia. The examination includes a complete blood count, a smear of peripheral blood, and a clinical evaluation. The results showed that the patient had central type pancytopenia, with a suspected etiology of aplastic anemia or myelodysplastic syndrome. Other differential diagnoses include vitamin B12 deficiency. Although a bone marrow biopsy is necessary to confirm the diagnosis, initial therapy with blood transfusions and nutritional improvements has shown an improvement in the patient's condition. The conclusion of this study is the importance of a thorough evaluation to identify the etiology of pancytopenia. Proper treatment should be based on the underlying cause, which will affect the prognosis and prevent recurrence. A comprehensive approach can improve patients' quality of life and reduce the risk of complications